(untitled) (International Journal of Engineering and Computer Science, 2015)
Most of the time people using internet for online transactions from one place to another place because of its cost effectiveness and ease of use. So it is necessary to ensure the security of such transaction but unfortunately an attacker can attack on system online or offline. Among a various kind of internet attacks, phishing is identified as a major security threat and all the prevention mechanisms failing in front of that, so prevention mechanism should be very strong. Phishing is defined as an identity theft attempt in order to obtain confidential and private information of individuals or companies for monetary or other gains. If these threats are not addressed thoroughly, people can’t trust online transactions that involve due authentication through credentials. A visual cryptography based technique will automatically preserve the privacy of captcha during registration. It is done by dividing the original image captcha having the password into two shares which are to be stored in different databases. The decryption is possible only when adversaries can provide both shares at a time. The individual shares can’t reveal the original captcha. In the proposed methodology discusses the security to the user share by implementing AES PKC5 Padding encryption algorithm which guarantees the confidentiality of the user share from attacks.